1984
DOI: 10.1128/aac.26.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lipopolysaccharide structure and permeability resistance in beta-lactam-resistant Pseudomonas aeruginosa

Abstract: Four ,-lactam-resistant permeability mutants of Pseudomonas aeruginosa PA0503 were studied. The resistance phenotypes were correlated to changes within the lipopolysaccharide. Two of the mutants, PCC1 and PCC19, were shown to differentiate between I-lactams on the basis of relative hydrophobicity. The more hydrophilic antibiotics were less effective at inhibiting these strains. This phenotype was correlated to the presence of mannose, in measurable quantities, in lipopolysaccharide isolated from these strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…In addition, we previously suggested that the LPS of P. aeruginosa may alter porin function (1). Godfrey et al also presented data suggesting that LPS influenced porin function in P. aeruginosa (6). In light of the data presented in this paper, it may be useful to reexamine the conclusions drawn from these studies.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, we previously suggested that the LPS of P. aeruginosa may alter porin function (1). Godfrey et al also presented data suggesting that LPS influenced porin function in P. aeruginosa (6). In light of the data presented in this paper, it may be useful to reexamine the conclusions drawn from these studies.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that mechanisms of resistance to nalidixic acid in P. aeruginosa involve alterations in replicative DNA synthesis in permeabilized cells and alterations in cell permeability as a result of mutations in the nalA and nalB loci, respectively (32 (1,3,6,7,19,22,27,29,37). No (27).…”
Section: Discussionmentioning
confidence: 99%
“…OMPs were isolated by the method of Hancock and Nikaido,lg as modified by Godfrey et a1., 20 . Protein concentration was determined by the method of Lowry21 with bovine serum albumin as a standard.…”
Section: Isolation and Characterisation Of Outer-membrane Proteins (Omentioning
confidence: 99%